Accumulation of coumaric acid is a key factor in tobacco continuous cropping obstacles - Jia, Meng; Wang, Xingsong; Zhu, Xuanquan; Du, Yu; Zhou, Peng; Wang, Ge; Wang, Na; Bai, Yuxiang (Frontiers in Plant Science, 2024)
Phenolic acids are believed to play a significant role in tobacco continuous cropping obstacles, but the strength and potential mechanisms of different phenolic acids remain unclear. This study evaluated the allelopathic effects of six phenolic acids with cumulative effects in our previous study and found that coumaric acid exhibited the strongest direct allelopathic effect. Exogenous coumaric acid significantly reduced soil pH and shifted the soil microbial community from fungi-dominated to bacteria-dominated. Simultaneously, the abundance of bacteria related to nutrient utilization (e.g., Flavisolibacter, Methylobacterium) and fungi related to disease resistance (e.g., Fusicolla, Clonostachys) gradually decreased, along with a reduction in soil catalase, urease, invertase, and acid phosphatase activities. Leaf MDA levels increased continuously with higher concentrations of coumaric acid, while the root resistance hormone (jasmonic acid and the jasmonate-isoleucine complex) levels show the opposite trend. These combined effects led to inhibited tobacco growth. This study provides theoretical guidance for precise mitigation of continuous cropping obstacles in future tobacco cultivation.